“It’s Important to Understand the Way of a Persion’s Development.”: the Image of Porfiry Petrovich in the Dostoyevsky’s Novel "Crime and Punishment" (Филологический класс, 2013)
The article is devoted to studying of the famous Dostoyevsky’s novel at school. The author offers system of tasks, gives the plan of the analysis of few episodes, specifies Porfiry Petrovitch's position in system of characters.